2017
DOI: 10.1016/j.aott.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Is the use of hemostatic matrix (Floseal) and alkylene oxide copolymer (Ostene) safe in spinal laminectomies? Peridural fibrosis assessment

Abstract: ObjectiveFailed Back Syndrome (FBS) is unacceptable relief of pain or recurrence of symptoms in patients after spinal surgery, such as laminectomy. One possible cause of FBS is peridural fibrosis (PF). PF is the overproduction of scar tissue adjacent to the dura mater. Bleeding can cause PF after laminectomy. Ostene is an alkylene oxide copolymer material used to stop bleeding from bony surfaces. Floseal is a gelatin thrombin matrix sealant used to assist fibrin formation and to promote coagulation.MethodsTota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(28 reference statements)
2
11
0
Order By: Relevance
“…Furthermore Ostene® is removed from the body unchanged while bone wax is not. Our results are in agreement with Gurcan et al, 23 who showed that the advantages of Ostene® over bone wax is that Ostene® is absorbed within two days, in addition to that it does not have adverse effects on healing and is excreted unchanged by the body. Nooh et al, 27 informed a foreign body reaction to bone wax in the form of granulomatous inflammation and fibrous encapsulation with the inhibition of bone healing and osteogenesis.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore Ostene® is removed from the body unchanged while bone wax is not. Our results are in agreement with Gurcan et al, 23 who showed that the advantages of Ostene® over bone wax is that Ostene® is absorbed within two days, in addition to that it does not have adverse effects on healing and is excreted unchanged by the body. Nooh et al, 27 informed a foreign body reaction to bone wax in the form of granulomatous inflammation and fibrous encapsulation with the inhibition of bone healing and osteogenesis.…”
Section: Resultssupporting
confidence: 93%
“…This revealed that Ostene® has an anti-fibrosis effect in agreement with results from other studies. 19,23 Regarding the histopathological analysis, abundant, poorly organized bony trabeculae with maturation of granulation tissue into the connective tissue was observed the control group during 2 nd week; while at the same period in the Ostene® group more organized granulation tissue with bone trabeculae which increased in number, thickness and organization was visible, in contrast to bone wax group who displayed less bone trabeculae in a disorganized manner, a phenomenon corroborated by other studies. 12…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Because the size of the defect in our study was small (5mm), this may explain why the granulation tissue was not seen clearly. A study by Gurcan et al, 28 showed Ostene® had antifibrosis effect. This finding is in agreement with our results.…”
Section: Discussionmentioning
confidence: 97%
“…This came in agreement with the study of Vestergaard et al as they found Ostene to stick well to the bone and acts as a mechanical obstacle which precludes blood emerge from bare spongy osseous tissue thus inducing hemostasis (24) . Further study showed that ostene is suitable to arrest bleeding as it is an inert hydrophilic material that does not interfere with coagulation properties, absorbed within 48hours and eliminated from the body unchanged (25) . When comparing ostene with gelfoam both clinically and experimentally, ostene appeared better than gelfoam in controlling bleeding with the latter inducing infection when left inside the socket.…”
Section: Discussionmentioning
confidence: 99%